2012
DOI: 10.1063/1.4765733
|View full text |Cite
|
Sign up to set email alerts
|

Studies on temperature dependent semiconductor to metal transitions in ZnO thin films sparsely doped with Al

Abstract: For a detailed study on the semiconductor to metal transition (SMT) in ZnO thin films doped with Al in the concentration range from 0.02 to 2%, we grew these films on (0001) sapphire substrates using sequential pulsed laser deposition. It was found that the Al concentration in the films increased monotonically with the ratio of ablation durations of the Alumina and ZnO targets used during the deposition. Using X-ray photo electron spectroscopy it was found that while most of the Al atoms occupy the Zn sites in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
14
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 27 publications
(58 reference statements)
3
14
0
Order By: Relevance
“…For the AZO films grown at high temperature, the agreement between the resistivities obtained by the different techniques is very good, producing values in the 10 to 1 mΩ-cm for the 150 ºC to 350 ºC samples, respectively, carrier densities over 10 20 cm -3 , and Hall mobilities between 6 and 30 cm 2 V -1 s -1 . These resistivities are at the higher end of the values often found in the literature [21,26,39]. Conversely, the resistivities obtained for annealed AZO films show significant discrepancies between the electrical and the optical measurements derived from the Drude model.…”
Section: Electrical Properties: Hall and Resistivitysupporting
confidence: 52%
See 1 more Smart Citation
“…For the AZO films grown at high temperature, the agreement between the resistivities obtained by the different techniques is very good, producing values in the 10 to 1 mΩ-cm for the 150 ºC to 350 ºC samples, respectively, carrier densities over 10 20 cm -3 , and Hall mobilities between 6 and 30 cm 2 V -1 s -1 . These resistivities are at the higher end of the values often found in the literature [21,26,39]. Conversely, the resistivities obtained for annealed AZO films show significant discrepancies between the electrical and the optical measurements derived from the Drude model.…”
Section: Electrical Properties: Hall and Resistivitysupporting
confidence: 52%
“…Das et al [39] showed that below an aluminium concentration of 0.2%, there is a very strong dependence of the carrier density and resistivity of the AZO films with the dopant density. In this regime, small fluctuations in the active dopants results in a metal-insulator transition, changing abruptly the electrical and optical properties of the material.…”
Section: Azo With Low Dopant Densitymentioning
confidence: 99%
“…These resistivities are at the higher end of the values often found in the literature [7]. Conversely, the resistivities obtained for annealed AZO films show significant discrepancies between the electrical and the optical measurements derived from the Drude model.…”
Section: Hall and Resistivitysupporting
confidence: 55%
“…The q(T) curves shown in Figures 4(a), 4(d), and 4(e), corresponding to the ALD-ZnO films grown at $150, 300, and 350 C, respectively, showed only semiconducting behaviour in the entire measurement temperature range, from room temperature down to liquid helium temperature. In contrast, a transition from metallic to semiconducting transport behaviour at lower temperatures 16,17,25,26 were observed in the q(T) curves shown in Figures 4(b) and 4(c) which correspond to the films grown at substrate temperatures of $200 and 250 C, respectively. The observed semiconducting behaviour in all the q(T) curves could not be fitted by the classical Arrhenius equation.…”
Section: Methodsmentioning
confidence: 55%